Assessing the Benefits of Mobile Application-Based Psychoeducation for Patients with Schizophrenia: A Randomized Controlled Trial - Jalaluddin Rumi,Junaid Rasool,Azal Jodat , Naeem Amjad, Naila Islam Tahir, Syed Ahmed Mahmud, (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
A randomized controlled trial evaluated the efficacy of a mobile application–basedpsychoeducation program for improving treatment adherence and symptom management among120 adult patients with schizophrenia. Participants were allocated to either the interventiongroup—receiving eight weeks of daily